EFFECTIVENESS OF VIRTUAL REALITY SIMULATION BASED TRAINING ON MOTOR SKILL DEVELOPMENT IN JUNIOR TENNIS PLAYERS - Santika Rentika Hadi; Rahmadhany Hananto Puriana; Riga Mardhika; Hayati; I Gede Dharma Utamayasa (Bidang Penelitian dan Pengembangan KONI Provinsi Bali, 2026)
Advances in sports technology, particularly Virtual Reality (VR), provide innovative training methods that allow athletes to practice motor skills in simulated and controlled environments. This study aimed to examine the effectiveness of Virtual Reality Simulation-Based Training on motor skill development in junior tennis players. The research was conducted at a junior tennis club in Singaraja, Bali, involving 20 junior athletes as research participants. This study employed an experimental approach using a pre-test and post-test design. The training program integrated virtual simulations of tennis movements, including stroke techniques, footwork coordination, reaction timing, and spatial awareness. Athletes participated in structured VR training sessions combined with conventional tennis practice over a determined training period. Motor skill performance was measured using standardized tennis motor skill tests that assessed coordination, agility, movement accuracy, and stroke execution. The results indicated a significant improvement in the motor skill performance of junior tennis players after participating in the Virtual Reality Simulation-Based Training program. The integration of VR technology allowed athletes to experience repetitive movement practice, immediate feedback, and immersive training scenarios that enhanced motor learning processes. In addition, VR-based training contributed to increased motivation and engagement among athletes during the training sessions. In conclusion, Virtual Reality Simulation-Based Training is an effective and innovative training approach for enhancing motor skill development in junior tennis players. The findings suggest that the integration of VR technology into tennis training programs can support coaches in creating more interactive, efficient, and technology-driven training environments that optimize motor skill acquisition among young athletes.